Course Design using an Authentic Studio Model / Restructuration de cours au moyen d'un authentique modèle de studio de design - Jay R Wilson (The Canadian Network for Innovation in Education (CNIE), 2013)
Educational Technology and Design 879 is a graduate course that introduces students to the basics of video design and production. In an attempt to improve the learning experience for students a redesign of the course was implemented for the summer of 2011 that incorporated an authentic design studio model. The design studio approach is based on the idea of working and learning in a shared space. Offering a course that employs a studio design model provides the opportunity for exchanging ideas, sharing artifacts, and developing community more deeply and more quickly. What makes this course offering different is the combination of authentic tasks incorporating both online and face-to-face design studio environments. This paper will describe how a studio design approach combined with an authentic learning design was implemented and what was learned. Educational Technology and Design 879 est un cours d'études supérieures initiant les étudiants aux rudiments de la conception et de la production vidéo. Pour améliorer l'expérience d'apprentissage, une refonte du cours a été entreprise à l'été 2011 en intégrant un authentique modèle de studio de design. L'approche « studio de design » repose sur l'idée d'un travail et d'un apprentissage réalisés dans un espace partagé. Un cours utilisant un modèle de studio de design offre la possibilité d'échanger des idées, de partager des artefacts et de développer une communauté plus en profondeur et plus rapidement. Ce qui rend ce cours unique est la combinaison de tâches authentiques qui incorporent des environnements de studio de design à la fois en ligne et en face à face. Cet article décrit comment une approche « studio de design » combinée à une conception d'apprentissage authentique a été mise en œuvre et ce qu'on en a appris.